Pemodelan Spektrum Gelombang di Pantai Barat hingga Selatan Indonesia - Bangguna, David S. V. L .; Zalukhu, Aisyah Christine; Laia, Debora; Harianja, Jhonson Andar (Jurnal Kelautan Tropis, 2025)
Wave spectrum modeling can describe the distribution of wave energy based on frequency and direction over a specific time period in the observed water area. Understanding the energy distribution from the wave spectrum is highly beneficial for designing structures that are stronger, more stable, and resistant to extreme ocean conditions. The aim of this research is to model the wave spectrum characteristics of the waters from the western to southern regions of Indonesia. The western coast of Sumatra Island to the southern coast of Papua Island was selected as the study area because these coastal regions are more exposed to wave propagation from the Indian Ocean, making them more vulnerable to wave impacts. The specific locations include Meulaboh Beach (West Aceh), Sorake (South Nias), Lais (North Bengkulu), Bunton (Cilacap), Jerman Beach (Bali), Walakiri (East Sumba), and Wendu (Merauke). The wave height analysis at the seven locations along the western to southern coasts of Indonesia shows that Walakiri Beach experiences higher wave heights compared to other locations, with wave heights of 4.8 m (West monsoon), 4.9 m (Transitional Season I), 5.7 m (East monsoon), and 4.3 m. During the Transitional Season II, the highest wave energy also occurs at Walakiri Beach. The wave energy values for the four consecutive seasons are: West monsoon (34.461 m²/Hz), Transitional Season I (35.911 m²/Hz), East monsoon (46.180 m²/Hz), and Transitional Season II (23.987 m²/Hz). The wave energy values are directly proportional to the wave heights—the higher the wave, the greater the energy it carries. This occurs because ocean waves are the result of accumulated wind energy that blows across the sea surface.   Pemodelan spektrum gelombang dapat menggambarkan distribusi energi gelombang berdasarkan frekuensi dan arah dalam jangka waktu tertentu pada daerah perairan yang diamati. Pemahaman penyebaran energi dari spektrum gelombang akan sangat membantu perancangan struktur yang lebih kuat, stabil, dan tahan terhadap kondisi laut ekstrem. Tujuan penelitian yaitu untuk memodelkan karakteristik spektrum gelombang dari perairan Barat hingga Selatan Indonesia. Pantai Barat pulau Sumatera hingga pantai Selatan pulau Papua dipilih untuk lokasi penelitian ini karena lokasi pantai ini lebih terbuka terhadap penjalaran gelombang dari Samudra Hindia, sehingga pantai lebih rentan terhadap gempuran gelombang. Lokasi tersebut yaitu pantai Meulaboh (Aceh Barat), Sorake (Nias Selatan), Lais (Bengkulu Utara), Bunton (Cilacap), Jerman (Bali), Walakiri (Sumba Timur), dan Wendu (Merauke). Hasil analisis tinggi gelombang pada tujuh lokasi di pantai Barat hingga Selatan Indonesia, menunjukkan bahwa tinggi gelombang di pantai Walakiri lebih tinggi dibandingkan dengan lokasi pantai yang lainnya yaitu 4,8 m (musim Barat), 4,9 m (musim Peralihan I), 5,7 m (musim Timur) dan 4,3 m. Saat musim Peralihan 2, energi gelombang terbesar terjadi juga di pantai Walakiri. untuk empat musim berturut-turut dari musim Barat (34,461 m2/hz), musim Peralihan 1 (35,911 m2/Hz), musim Timur (46,180 m2/Hz), musim Peralihan 2 (23,987 m2/Hz). Nilai energi gelombang yang terjadi berbanding lurus dengan tinggi gelombangnya, semakin tinggi gelombang maka energi gelombangnya juga semakin besar, hal ini terjadi karena gelombang di laut merupakan hasil dari akumulasi energi angin yang berhembus di atas permukaan air laut.